Implementasi Indigenous Product Attractiveness Melalui Inovasi produk dan Digital Marketing Guna Peningkatan kinerja Pemasaran UMKM Batik Gemeksekti Kebumen - Zakiyah, Tuti; Kabul Trifiyanto; Wahyuni Windasari (Politeknik Negeri Jember, 2024)
Gemeksekti in Kebumen district has many small batik industries, batik craftsmen produce various kinds of batik motifs. The large amount of competition from batik craftsmen, both from Kebumen Regency and from other areas, requires batik craftsmen in Gemeksekti Village to determine strategies so that batik products from Gemeksekti Village continue to increase production and sales. One of the efforts to improve the marketing performance of batik klister MSMEs is indigenous product attractiveness, the attractiveness of products inherent in unique products resulting from indigenous knowledge reflected in local culture is able to improve marketing strategies so that marketing performance will increase. The method used in this activity is training and mentoring. Training includes increasing product value through design innovation, production standardization and brand creation. Mentoring is focused on digital marketing, including creating e-commerce accounts, managing social media, and developing product catalogues. The research results show that training and mentoring activities have succeeded in increasing the knowledge and skills of community members in terms of digital marketing and product innovation. Apart from that, this activity also succeeded in increasing the selling value of batik products and expanding market reach.